2013
DOI: 10.4300/jgme-d-13-00033.1
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Critical Care Skills After Simulation-Based Mastery Learning

Abstract: Background Whether cognitive and patient care skills attained during simulation-based mastery learning (SBML) are retained is largely unknown. Objective We studied retention of intensive care unit (ICU) clinical skills after an SBML boot camp experience. Methods Forty-seven postgraduate year (PGY)-1 residents completed SBML intervention designed to increase p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 27 publications
(29 reference statements)
5
27
0
1
Order By: Relevance
“…A systematic review and meta‐analysis of quantitative outcomes of mastery learning simulation‐based medical education (SBME) in comparison with no intervention showed that SBME was associated with large effects on skills and moderate effects on patient outcomes when compared to no intervention . Simulation‐based learning can lead to improved retention of patient care skills . At our institution, all trainees attend NRP prior to the start of their intern year with recertification at the end of their second year of residency.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta‐analysis of quantitative outcomes of mastery learning simulation‐based medical education (SBME) in comparison with no intervention showed that SBME was associated with large effects on skills and moderate effects on patient outcomes when compared to no intervention . Simulation‐based learning can lead to improved retention of patient care skills . At our institution, all trainees attend NRP prior to the start of their intern year with recertification at the end of their second year of residency.…”
Section: Introductionmentioning
confidence: 99%
“…44 For most individuals participating in resuscitation courses, clinical resuscitations are rare events, emphasizing the importance of learning from simulated scenarios so that they are able to act when the real-life events occur. 45 By engaging learners in scenarios and guiding them through a constructive debriefing, instructors can maximize knowledge transfer to real-life events. Critical to this learning process is the notion that the experience is not enough to promote practice change.…”
Section: Educational Designmentioning
confidence: 99%
“…In the 15 studies reviewed in the above‐mentioned meta‐analysis, none reported the impact of the educational intervention on physician practice or behavior. A few recent studies describe retention of procedural skills during the first year after a Boot Camp, with a maximum follow‐up time of 12 months . One study described improved surgical skills in a group of orthopedic residents up to 18 months after completion of a Boot Camp compared to a group of contemporary second year residents and similar skill level to a contemporary group of third year residents .…”
Section: Discussionmentioning
confidence: 99%